1995
DOI: 10.1902/jop.1995.66.8.679
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Volatile Sulphur Compounds and Certain Oral Health Measurements in the General Population

Abstract: Oral malodor was measured using a portable sulphide monitor in 2,672 individuals aged 18 to 64 years. In addition, dental (DMFT) and periodontal conditions (CPITN and attachment loss), dental plaque, and tongue coating status were assessed. Before clinical examination, subjects were interviewed about their oral health habits, smoking habits, and medical history. Data on volatile sulphur compounds (VSC) were analyzed by gender, age group, and time of measurement. There were no significant differences observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
384
11
36

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(470 citation statements)
references
References 18 publications
27
384
11
36
Order By: Relevance
“…Population-based studies showed variations in prevalence estimates of halitosis, ranging between 6% and 72%. 2,23,24,25 In comparison with other populations, the prevalence observed in this sample may be considered low. However, this prevalence of approximately 22% may have an important impact, considering that the population studied is composed of dental students.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Population-based studies showed variations in prevalence estimates of halitosis, ranging between 6% and 72%. 2,23,24,25 In comparison with other populations, the prevalence observed in this sample may be considered low. However, this prevalence of approximately 22% may have an important impact, considering that the population studied is composed of dental students.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, it is noteworthy that over 90% of the participants reported cleaning their tongue at least once a day, a habit that can have a significant impact in reducing halitosis, since the tongue plays an important role in halitosis, mainly in individuals with good oral health. 24 The occurrence of self-reported halitosis was higher in initial semester students than in final semester students. The chance of detecting self-reported halitosis was 55% lower in the students from the last three semesters than in those from the first three semesters.…”
Section: Discussionmentioning
confidence: 93%
“…Volatile sulfur compounds are primarily produced through the putrefactive activity of bacteria present in saliva, in periodontal pockets, on the tongue surface, and in other areas (1,(3)(4)(5). In particular, the tongue dorsum has been implicated as a major cause for oral malodor (5).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of malodor comprises insufficient saliva flow, periodontal diseases, excessive microbial colonization of the tongue and poor oral hygiene (1)(2)(3). Malodorous volatile sulfur compounds originate from putrefactive activity of microorganisms in oral cavities, saliva, and periodontal pockets and on the tongue surface (1,4,5). Among the large number of bacterial species populating the oral cavity, Gram-negative anaerobic bacteria, including Porphyromonas spp., Veillonella spp., Prevotella spp., Fusobacterium spp., Tannerella forsythia, and Treponema denticola represent the microorganisms predominantly involved in VSC generation (6)(7)(8).…”
mentioning
confidence: 99%
“…A variety of index systems for tongue coating has been developed over the years. Miyazaki et al divides the tongue into three sections and the presence or absence of tongue coating is registered as follows: Score 0 = none visible, Score 1 = less than one third of tongue dorsum is covered, Score 2 = between one and two thirds, Score 3 = more than two thirds [13]. Winkel et al divides the tongue into six sections, three in the posterior and three in the anterior part of the tongue.…”
mentioning
confidence: 99%